“Proyecto de Factibilidad para la implementación de un local de servicio técnico de celulares en el cantón Quito parroquia El Condado, Pichincha” - Merchán Alvarez., Evelin Andrea (2024)
This research work focuses on the feasibility of implementing a cell phone technical service center in the El Condado parish, Quito. A market study was conducted, revealing a high potential unmet demand, with 75% of respondents having previously used technical services and 85% interested in acquiring them locally. The current supply, although robust, shows areas of opportunity for a new competitor, especially in terms of innovation and customer service. The technical study defined the project size, installed capacity, and production processes, including plant layout and project engineering. The administrative study established the company's legal and organizational structure, including the articles of incorporation and function manuals. The financial study projected an initial investment of $33,453.05, including fixed assets, working capital, and production costs. The financial analysis, using Net Present Value (NPV) and Internal Rate of Return (IRR), demonstrated the project's viability, with a positive NPV of $3,598.01 and an IRR of 14.37%, exceeding the reference rate of 9.97%. The payback period was estimated at 4 years, 5 months, and 19 days.